Atendimento educacional especializado e o desenvolvimento do estudante com Transtorno Espectro Autista na educação básica - Gomes, Ingrid Cristina de Arruda (Universidade Federal do Tocantins, 2025)
In view of the importance of the Specialized Service Room for autistic students in Basic Education. The present research was carried out as a necessary requirement for the completion of the degree in Pedagogy at the Federal University of Tocantins (UFT). The methodology used consists of a bibliographic review, which encompasses scientific studies, books and official documents on the subject, it is done thinking about the pedagogical practices that contribute to the learning of these students. Its general objective was: To make a survey of dissertations, scientific articles, books among other official documents that discuss Autism and how the Specialized Educational Service (AEE) Specialized Service Room (SAE) contributes to the development of the Autistic child in basic education. The following question was asked: How does the specialized care room contribute to the development of the Autistic student in Basic Education? The study is justified by the need to broaden the understanding of pedagogical practices aimed at serving students with Autism Spectrum Disorder (ASD) and to identify the possible contributions that a specialized care room (SAE) can offer to the integral development of these students. It is hoped that the results of this research can help in understanding the benefits that an adapted school environment can bring to the development of cognitive, social and emotional skills of children with ASD. The study also aims to contribute to teacher training, providing theoretical and practical subsidies for the effective inclusion of these students in the school environment. The main points discussed in this work are: the challenges of school inclusion; the importance of the adapted environment for the development of children with ASD; and the pedagogical strategies that can be used in a specialized service room.